2018
DOI: 10.26776/ijemm.03.02.2018.03
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emission of Broiler Chicken Production in Malaysia using Life Cycle Assessment Guidelines: A Case Study

Abstract: The aim of this research was to evaluate the level of greenhouse gas emission from broiler chicken farming industry in Malaysia. In order to achieve that, Life Cycle Assessment method was chosen as a framework to complete the task. A case study was conducted at a broiler chicken farm to gather the data and information related to the broiler chicken production. Cradle-to-gate assessment including distribution stage was conducted based on the ISO14040/1044 guidelines. Inventory data for this case study was gathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
3
3
0
1
Order By: Relevance
“…For system A, feeds (CO2 and N2O) is the GWP driver at 87.1%, which concurs with other LCA studies involving intensive broiler chicken production [5][6][7][8][9]. Similarly, in system B, feeds (50.7%) is the driver followed by beddings (22.6%).…”
Section: Results and Discussion 1) Life Cycle Inventorysupporting
confidence: 86%
See 1 more Smart Citation
“…For system A, feeds (CO2 and N2O) is the GWP driver at 87.1%, which concurs with other LCA studies involving intensive broiler chicken production [5][6][7][8][9]. Similarly, in system B, feeds (50.7%) is the driver followed by beddings (22.6%).…”
Section: Results and Discussion 1) Life Cycle Inventorysupporting
confidence: 86%
“…For environmental impacts of chicken production, various life cycle assessment studies have been done among developed nations like in USA, Europe, Brazil, Australia [3][4][5][6][7] and a few among Asia [8][9]. Common key finding is that environmental impacts mostly come from feed production, manure management, and utilization of fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Agroindustri ayam ras pedaging merupakan salah satu industri yang berkontribusi terhadap kerusakan lingkungan, diantaranya emisi gas rumah kaca (Suffian et al, 2018). Lima et al (2019) menyatakan bahwa proses produksi ayam ras pedaging di peternakan menyumbang emisi gas rumah kaca karena manajemen manure sebagai kontributor terbesar dalam menghasilkan emisi gas metana (CH4) dan dinitrogen oksida (N2O).…”
Section: Abstrakunclassified
“…Soybean meal was found to be the largest contributor to the environmental impact of feed due to transport, land transformation, and mineral fertilizer application (Cesari et al, 2017). A study by Suffian et al (2018) showed that in modern broiler production, manure produces most emissions of CO2, feed produces most emissions of CH4, and bedding produces most emissions of N2O. Controlling GHG emissions from broiler chicken production is essential for reducing the agriculture sector's impact on global warming.…”
Section: Introductionmentioning
confidence: 99%